A magnetic biocarbon composite adsorbent and its preparation method and application in adsorbing heavy metal chromium (VI)

By preparing magnetic biocarbon composite adsorbents, using surface chemical modification and the combination of magnetic nanospheres, the problems of limited surface properties and groups of existing biocarbon adsorbents are solved, and efficient adsorption and removal of heavy metal chromium (VI) are achieved. , and supports the recycling and reuse of adsorbents.

CN116078353BActive Publication Date: 2025-02-14XI AN JIAOTONG UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211627722.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-16
Publication Date
2025-02-14
Estimated Expiration
2042-12-16

AI Technical Summary

Technical Problem

The surface properties and groups of existing biochar adsorbents are limited, resulting in limited adsorption and removal of heavy metal chromium (VI) and cannot completely remove heavy metal chromium (VI) in the soil.

Method used

By preparing magnetic biocarbon composite adsorbents, biochar is prepared using waste biomass materials, and amino and carboxy groups are added through surface chemical modification, combining carboxy ferromagnetic nanospheres to form a covalent bonded magnetic biocarbon composite Adsorbent.

Benefits of technology

It has achieved efficient adsorption and removal of heavy metal chromium (VI). The removal rates of adsorbents in heavy metal chromium (VI) contaminated water and soil reached 90.4% and 88.5%, respectively, and have the convenience of magnetic separation, supporting the adsorbents. Efficient recycling and reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116078353B_ABST
    Figure CN116078353B_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic biochar composite adsorbent, a preparation method thereof, and an application of adsorbing heavy metal chromium (VI). The scheme selects waste biomass materials to prepare biochar, and the porous structure of biochar increases its specific surface area to provide more effective adsorption sites for heavy metal chromium ions. A layer of amino groups is modified on the surface of biochar by surface chemical modification to modify the amino groups, and then covalently bonded with carboxyl-modified magnetic balls with rich carboxyl groups on the surface through amidation reaction. The magnetic biochar changes the surface properties of activated carbon by loading magnetic nanoparticles into activated carbon, so that there are a large number of active sites to increase chemical adsorption, and covalent bonding increases the recyclability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biochar modification and nano material preparation, and relates to a magnetic biochar composite adsorbent and a preparation method thereof and application of the adsorbent for heavy metal chromium (VI). Background Art

[0002] Soil not only provides mechanical support for plant growth, but also provides the necessary fertility elements such as water, fertilizer, air, and heat for plant growth and development. Due to the rapid population growth and rapid industrial development, solid waste is continuously piled and dumped on the soil surface, harmful wastewater is continuously infiltrating into the soil, and harmful gases and floating dust in the atmosphere are continuously falling into the soil with rain, resulting in serious soil pollution.

[0003] Chromium compounds are widely used in electroplating, metal processing, leather making, dyes, steel and chemical industries. The chromium content of chromium-containing wastewater discharged by the leather making industry can reach 410 ml / L. Industrial chromium slag can pollute many rivers after dissolving in water. Chromium has been considered as a serious environmental pollutant. Chromium usually exists in trivalent and hexavalent forms in nature. In organisms, it is mainly trivalent chromium, and in water and soil, it exists in hexavalent form. Hexavalent chromium has the greatest toxic effect on organisms and humans. When irrigating farmland with chromium-containing wastewater, chromium ions can accumulate in the soil, which will inhibit the growth and development of crops. Because of excessive accumulation, it can bind to the protein of the cell protoplasm in the plant body and cause cell death. Hexavalent chromium is more easily absorbed by the human body and can accumulate in the body. Excessive chromium is carcinogenic to humans and is a strong mutagenic substance that can induce lung cancer and nasopharyngeal cancer. Therefore, the removal of heavy metal chromium (VI) in soil is of great significance.

[0004] Biochar (BC) refers to a type of refractory, stable, highly aromatic, carbon-rich solid material generated by slow pyrolysis of biomass at high temperature in an oxygen-deficient or oxygen-free atmosphere. It has significant advantages such as large specific surface area, high porosity, multiple functional groups, and stable physical and chemical properties. It can adsorb heavy metal chromium (VI) ions through electrostatic attraction, precipitation, surface complexation, and surface adsorption, and has excellent adsorption and removal capabilities. However, due to the limited surface properties and group types of biochar, it is necessary to enhance the performance of biochar through modification by different methods to meet different needs. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a magnetic biochar composite adsorbent and a preparation method thereof and an application for adsorbing heavy metal chromium (VI), so as to solve the technical problem that the existing biochar adsorbent has limited surface properties and groups, resulting in limited adsorption and removal capacity, thereby failing to completely remove heavy metal chromium (VI) in the soil.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention discloses a method for preparing a magnetic biocarbon composite adsorbent, comprising the following steps:

[0008] 1) washing, drying, crushing and sieving the waste biomass material to obtain a biochar raw material, mixing the biochar raw material with an alkaline solution to remove impurities, and then washing and drying to obtain alkaline biochar;

[0009] 2) fully mixing the alkaline biochar with a methanol solution of polyethyleneimine, and then performing a cross-linking reaction with a glutaraldehyde solution to obtain amino-modified biochar;

[0010] 3) ultrasonically dispersing the carboxyferroferric oxide magnetic nanospheres into 2-morpholineethanesulfonic acid buffer, and adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, continuing to ultrasonically disperse them uniformly, and then shaking them on a shaker for 10 to 30 minutes, centrifuging, and obtaining activated carboxyferroferric oxide nanoparticles;

[0011] 4) The amino-modified biochar prepared in step 2) is dispersed in a buffer solution, and the activated carboxyl ferroferric oxide nanoparticles prepared in step 3) are added, and after ultrasonic mixing, the mixture is shaken overnight on a shaker, and the product is magnetically separated, washed, and dried to obtain a magnetic biochar composite adsorbent.

[0012] Preferably, in step 1), the ratio of the amount of biochar raw material to the alkaline solution is (20-50) g: (100-300) mL; the biochar raw material and the alkaline solution are stirred at room temperature at a stirring speed of 120-180 rpm for 1-3 hours to remove impurities in the biochar raw material; the biochar raw material is washed with water until the eluent is neutral, and the drying is carried out at 30-80°C for 12 hours.

[0013] Preferably, in step 2), the dosage ratio of alkaline biochar to the methanol solution of polyethyleneimine is (20-50) g: (50-200) mL; the mass concentration of the methanol solution of polyethyleneimine is 5%-20%, and the mixing is carried out by stirring at a speed of 120-180 rpm for 24 hours.

[0014] Preferably, in step 2), the ratio of alkaline biochar to glutaraldehyde solution is (20-50) g: (100-200) mL; the mass concentration of glutaraldehyde solution is 1%-5%, and the cross-linking reaction is stirred at a speed of 120-180 rpm for 30-60 min.

[0015] Preferably, in step 3), the usage ratio of carboxyl-modified ferrosoferric oxide nanomaterial, 2-morpholineethanesulfonic acid buffer, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is (120-150) mg: (50-80) mL: (400-500) mg: (700-750) mg.

[0016] Preferably, in step 3), the carboxyferroferric oxide magnetic nanospheres are synthesized by a one-step hydrothermal method, and the specific method is as follows: ferric chloride, sodium acetate, sodium polyacrylate and diethylene glycol are hydrothermally reacted at 180-210° C. for 9-12 hours in a dosage ratio of (0.7-1.2) g: (2.0-4.0) g: (50-150) mg: (25-35) mL, and then washed and dried to obtain carboxyferroferric oxide magnetic nanospheres.

[0017] Preferably, in step 4), the buffer solution is PBS buffer, and the usage ratio of amino-modified biochar to PBS buffer is (80-120) mg: (50-80) mL.

[0018] Preferably, the waste biomass material is corn straw, wheat straw or rice husk; and the alkaline solution is 1-6 mol / L KOH solution.

[0019] The invention also discloses a magnetic biocarbon composite adsorbent prepared by the preparation method.

[0020] The present invention also discloses the application of the magnetic bio-carbon composite adsorbent in the adsorption of heavy metal chromium (VI). The magnetic bio-carbon composite adsorbent is treated in heavy metal chromium (VI) contaminated water for 48 hours, and the removal rate of heavy metal chromium (VI) ions reaches 90.4%; the magnetic bio-carbon composite adsorbent is treated in heavy metal chromium (VI) contaminated soil for 48 hours, and the removal rate of heavy metal chromium (VI) ions reaches 88.5%.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The preparation method of the magnetic biochar composite adsorbent disclosed in the present invention comprises the following steps: selecting waste biomass materials to prepare biochar; the porous structure of the biochar increases its specific surface area and can provide more effective adsorption sites for heavy metal chromium (VI) ions; a layer of amino groups is modified on the surface of the biochar by surface chemical modification to modify the biochar to amino groups; and then the biochar is covalently bonded to carboxyl-modified magnetic balls with rich carboxyl groups on the surface by amidation reaction; the magnetic biochar changes the surface properties of the activated carbon by loading magnetic nanoparticles into the activated carbon, thereby providing a large number of active sites to increase chemical adsorption; and the covalent bonding increases the recyclability of the material.

[0023] The novel magnetic biochar composite adsorbent prepared by the present invention through functional modification and surface modification has both the excellent heavy metal chromium (VI) adsorption and removal ability of biochar and the excellent magnetic separation of magnetic nanoparticles, which can realize the efficient recovery and reuse of the adsorbent in the soil, and is in line with the development concept of green chemistry. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a transmission electron micrograph of carboxyl ferroferric oxide nanoparticles synthesized in Example 1 of the present invention;

[0025] Figure 2 This is a transmission electron microscope image of the covalent magnetic biochar prepared in Example 1 of the present invention;

[0026] Figure 3 The adsorption efficiency of the covalent magnetic biochar prepared in Example 1 of the present invention on heavy metal chromium (VI). DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0028] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0029] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0030] Example 1

[0031] (1) washing corn stalks with deionized water to remove surface impurities, drying them to constant weight, crushing them with a grinder, and passing them through a 50-100 mesh sieve to obtain biochar;

[0032] (2) 240 mL of alkaline solution was mixed with 50 g of biochar and stirred at 160 rpm for 3 h at room temperature to remove impurities in the biochar;

[0033] (3) The biochar was rinsed with deionized water until the pH of the eluate was about 7.0. The wet biochar was dried in an oven at 80 °C for 12 h and then stored in a desiccator before use to obtain alkaline biochar;

[0034] (4) Alkaline biochar was added to 200 mL of 20% (w / v) PEI / methanol solution and stirred at 160 rpm for 24 h;

[0035] (5) Immediately transfer the stirred biochar to 200 mL of 5% (w / v) glutaraldehyde solution for crosslinking. Stir the solution at 160 rpm for 60 min. Then, wash with deionized water to obtain amino-modified biochar;

[0036] (6) 1.1 g of ferric chloride, 2.5 g of sodium acetate, 70 mg of sodium polyacrylate and 25 mL of ethylene glycol were placed in a reaction kettle and reacted at 190° C. for 12 h. After the reaction was completed, the reaction product was washed and vacuum dried to obtain carboxylated iron oxide magnetic nanospheres with rich carboxyl groups on the surface;

[0037] (7) 150 mg of carboxyferroferric oxide magnetic nanospheres ( Figure 1 ) was ultrasonically dispersed in 80 mL of MES (2-morpholineethanesulfonic acid) buffer solution, and then 480 mg of EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride) and 700 mg of NHS (N-hydroxysuccinimide) were added and ultrasonicated for 40 seconds, and then placed in a shaker at 37°C for 30 minutes, and quickly centrifuged to obtain activated carboxyl ferric oxide nanoparticles; at the same time, 100 mg of amino-modified biochar was ultrasonically dispersed in 50 mL of PBS buffer, and then the activated carboxyl ferric oxide nanoparticles were added, quickly ultrasonicated, and shaken at 37°C overnight, and then magnetically separated and washed with water and ethanol for 3 times, and then placed in an oven at 60°C for 12 hours to obtain covalently bound magnetic biochar ( Figure 2 ), that is, the target product magnetic biocarbon composite adsorbent.

[0038] In order to verify the adsorption performance of the magnetic biocarbon composite adsorbent prepared in this example for heavy metal chromium (VI), the following tests were performed:

[0039] (1) A 300 mg / L heavy metal chromium (VI) solution was prepared, and the magnetic biochar composite adsorbent prepared in this example was added to the heavy metal chromium (VI) solution at a dosage of 0.8 g / L. The solution was placed in a shaker and shaken at 160 r / min. 3 mL of the sample was taken at intervals, and the sample was filtered through a filter membrane. The heavy metal chromium (VI) content was determined by an ultraviolet spectrophotometer ( Figure 3 );

[0040]

[0041] Where R (%) is the removal rate of heavy metal chromium (VI) ions, C0 is the total heavy metal chromium (VI) concentration in the initial solution (mg / L), C e It is the concentration of heavy metal chromium (VI) ions in the solution at a certain time (mg / L).

[0042] (2) Prepare heavy metal contaminated soil: weigh 5 g of chromium contaminated soil and place it in a 50 mL centrifuge tube. Add ultrapure water and 1 g of magnetic biochar nanomaterial. Incubate the tube at 25 °C for 24 h and separate it with a magnetic bar that can absorb substances. Dry and digest the remaining soil. Determine the heavy metal chromium (VI) content in the filtrate using the ICP-OES method. The heavy metal chromium (VI) ion removal rate is 83.5%.

[0043] Example 2

[0044] (1) The corn stalks were washed with deionized water to remove surface impurities, dried to constant weight, crushed with a grinder, and passed through a 50-100 mesh sieve;

[0045] (2) 100 mL of alkaline solution was mixed with 20 g of biochar and stirred at 160 rpm for 1 h at room temperature to remove impurities in the biochar;

[0046] (3) The biochar was rinsed with deionized water until the pH of the eluate was about 7.0. The wet biochar was dried in an oven at 30 °C for 12 h and then stored in a desiccator before use to obtain alkaline biochar;

[0047] (4) Alkaline biochar was added to 50 mL of 5% (w / v) PEI / methanol solution and stirred at 160 rpm for 24 h;

[0048] (5) Immediately transfer the stirred biochar to 100 mL of 1% (w / v) glutaraldehyde solution for crosslinking. Stir the solution at 160 rpm for 30 min. Then, wash with deionized water to obtain amino-modified biochar;

[0049] (6) 1.2 g of ferric chloride, 3.5 g of sodium acetate, 90 mg of sodium polyacrylate and 30 mL of ethylene glycol were placed in a reaction kettle and reacted at 180° C. for 10 h. After the reaction was completed, the reaction product was washed and vacuum dried to obtain carboxylated ferroferric oxide magnetic nanospheres with a carboxyl-rich surface.

[0050] (7) 143 mg of carboxyferroferric oxide magnetic nanospheres were ultrasonically dispersed in 80 mL of MES (2-morpholineethanesulfonic acid) buffer solution, and 450 mg of EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride) and 720 mg of NHS (N-hydroxysuccinimide) were added to the above solution system and ultrasonication was continued for 25 seconds. The solution was then placed in a shaker at 37°C for 20 minutes and centrifuged quickly to obtain activated carboxyferroferric oxide nanoparticles. At the same time, 120 mg of amino-modified biochar was ultrasonically dispersed in 60 mL of PBS buffer, and the activated carboxyferroferric oxide nanoparticles were added, ultrasonicated quickly, and shaken in a shaker at 37°C overnight. The solution was magnetically separated and washed twice with water and ethanol, and then dried in an oven at 40°C for 24 hours to obtain a magnetic biochar composite adsorbent.

[0051] In order to verify the adsorption performance of the magnetic biocarbon composite adsorbent prepared in this example for heavy metal chromium (VI), the following tests were performed:

[0052] (1) A 300 mg / L heavy metal chromium (VI) solution was prepared, and a magnetic biochar composite adsorbent was added to the solution at a dosage of 0.8 g / L. The solution was placed in a shaker and shaken at 160 r / min. 3 mL of samples were taken at intervals, and the samples were filtered through a filter membrane. The content of heavy metal chromium (VI) in the heavy metal chromium (VI) solution after adsorption by the adsorbent was determined using an ultraviolet spectrophotometer;

[0053]

[0054] Where R (%) is the removal rate of heavy metal chromium (VI) ions, C0 is the total heavy metal chromium (VI) concentration in the initial solution (mg / L), C e It is the concentration of heavy metal chromium (VI) ions in the solution at a certain time (mg / L).

[0055] (2) Prepare heavy metal chromium (VI) contaminated soil: weigh 5 g of chromium-contaminated soil and place it in a 50 mL centrifuge tube. Add ultrapure water and then add 0.4 g of the magnetic biochar composite adsorbent prepared in this example. Flip and shake at 25° C. for 48 h. Separate with a magnetic bar that can absorb substances. Dry and digest the remaining soil. Use ICP-OES to determine the heavy metal chromium (VI) content in the filtrate. The heavy metal chromium (VI) ion removal rate is 88.3%.

[0056] Example 3

[0057] (1) The wheat straw was washed with deionized water to remove surface impurities, dried to constant weight, crushed with a grinder, and passed through a 60-mesh sieve;

[0058] (2) 200 mL of alkaline solution was mixed with 40 g of biochar and stirred at 160 rpm for 2 h at room temperature to remove impurities in the biochar;

[0059] (3) The biochar was rinsed with deionized water until the pH of the eluate was about 7.0. The wet biochar was dried in an oven at 50 °C for 12 h and then stored in a desiccator before use to obtain alkaline biochar;

[0060] (4) Alkaline biochar was added to 100 mL of 15% (w / v) PEI / methanol solution and stirred at 160 rpm for 24 h;

[0061] (5) Immediately transfer the stirred biochar to 130 mL of 3% (w / v) glutaraldehyde solution for crosslinking. Stir the solution at 160 rpm for 60 min. Then, wash with deionized water to obtain amino-modified biochar;

[0062] (6) 0.9 g of ferric chloride, 4.0 g of sodium acetate, 120 mg of sodium polyacrylate and 27 mL of ethylene glycol were placed in a reaction kettle and reacted at 200° C. for 9 h. After the reaction was completed, the reaction product was washed and vacuum dried to obtain carboxylated ferroferric oxide magnetic nanospheres with a carboxyl-rich surface.

[0063] (7) 135 mg of carboxyferroferric oxide magnetic nanospheres were ultrasonically dispersed in 65 mL of MES (2-morpholineethanesulfonic acid) buffer solution, and 490 mg of EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride) and 720 mg of NHS (N-hydroxysuccinimide) were added to the above solution system and ultrasonication was continued for 35 seconds. The solution was then placed in a shaker at 37°C for 15 minutes and rapidly centrifuged to obtain activated carboxyferroferric oxide nanoparticles. At the same time, 100 mg of amino-modified biochar was ultrasonically dispersed in 80 mL of PBS buffer, and the activated carboxyferroferric oxide nanoparticles were added thereto. The solution was rapidly ultrasonicated and shaken at 37°C overnight. The solution was magnetically separated and washed with water and ethanol three times. The solution was then dried in an oven at 60°C for 20 hours to obtain a magnetic biochar composite adsorbent.

[0064] In order to verify the adsorption performance of the magnetic biocarbon composite adsorbent prepared in this example for heavy metal chromium (VI), the following tests were performed:

[0065] (1) A 300 mg / L heavy metal chromium (VI) solution was prepared, and the magnetic biochar composite adsorbent prepared in this example was added to the above solution at a dosage of 0.8 g / L. The solution was placed in a shaker and shaken at 160 r / min. 3 mL of samples were taken at intervals, and the samples were filtered through a filter membrane. The content of heavy metal chromium (VI) in the heavy metal chromium (VI) solution after adsorption by the adsorbent was determined using an ultraviolet spectrophotometer;

[0066]

[0067] Where R (%) is the removal rate of heavy metal chromium (VI) ions, C0 is the total heavy metal chromium (VI) concentration in the initial solution (mg / L), C e It is the concentration of heavy metal chromium (VI) ions in the solution at a certain time (mg / L).

[0068] (2) Prepare heavy metal chromium (VI) contaminated soil: weigh 5 g of chromium-contaminated soil and place it in a 50 mL centrifuge tube. Add ultrapure water and then add 0.7 g of the magnetic biochar composite adsorbent prepared in this example. Flip and shake at 25° C. for 48 h. Separate with a magnetic bar that can absorb substances. Dry and digest the remaining soil. Use ICP-OES to determine the heavy metal chromium (VI) content in the filtrate. The heavy metal chromium (VI) ion removal rate is 86.1%.

[0069] Example 4

[0070] (1) washing the rice husk with deionized water to remove surface impurities, drying it to constant weight, crushing it with a grinder, and passing it through an 80-mesh sieve;

[0071] (2) 100 mL of alkaline solution was mixed with 30 g of biochar and stirred at 160 rpm for 1 h at room temperature to remove impurities in the biochar;

[0072] (3) The biochar was rinsed with deionized water until the pH of the eluate was about 7.0. The wet biochar was dried in an oven at 40 °C for 12 h and then stored in a desiccator before use to obtain alkaline biochar;

[0073] (4) Alkaline biochar was added to 50 mL of 5% (w / v) PEI / methanol solution and stirred at 160 rpm for 24 h;

[0074] (5) Immediately transfer the stirred biochar to 100 mL of 2% (w / v) glutaraldehyde solution for crosslinking. Stir the solution at 160 rpm for 40 min. Then, wash with deionized water to obtain amino-modified biochar.

[0075] (6) 0.7 g of ferric chloride, 2.8 g of sodium acetate, 150 mg of sodium polyacrylate and 33 mL of ethylene glycol were placed in a reaction kettle and reacted at 190° C. for 10 h. After the reaction was completed, the reaction product was washed and vacuum dried to obtain carboxylated iron oxide magnetic nanospheres with rich carboxyl groups on the surface;

[0076] (7) 130 mg of carboxyferroferric oxide magnetic nanospheres were ultrasonically dispersed in 50 mL of MES (2-morpholineethanesulfonic acid) buffer solution, and 480 mg of EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride) and 725 mg of NHS (N-hydroxysuccinimide) were added to the above solution system and ultrasonication was continued for 30 seconds. The solution was then placed in a shaker at 37°C for 25 minutes and centrifuged quickly to obtain activated carboxyferroferric oxide nanoparticles. At the same time, 90 mg of amino-modified biochar was ultrasonically dispersed in 60 mL of PBS buffer, and the activated carboxyferroferric oxide nanoparticles were added, ultrasonicated quickly, and shaken in a shaker at 37°C overnight. The solution was magnetically separated and washed twice with water and ethanol, and then dried in an oven at 50°C for 24 hours to obtain a magnetic biochar composite adsorbent.

[0077] In order to verify the adsorption performance of the magnetic biocarbon composite adsorbent prepared in this example for heavy metal chromium (VI), the following tests were performed:

[0078] (1) A 300 mg / L heavy metal chromium (VI) solution was prepared, and the magnetic biochar composite adsorbent prepared in this example was added to the above solution at a dosage of 0.8 g / L. The solution was placed in a shaker and shaken at 160 r / min. 3 mL of samples were taken at intervals, and the samples were filtered through a filter membrane. The content of heavy metal chromium (VI) in the heavy metal chromium (VI) solution after adsorption by the adsorbent was determined using an ultraviolet spectrophotometer;

[0079]

[0080] Where R (%) is the removal rate of heavy metal chromium (VI) ions, C0 is the total heavy metal chromium (VI) concentration in the initial solution (mg / L), C e It is the concentration of heavy metal chromium (VI) ions in the solution at a certain time (mg / L).

[0081] (2) Prepare heavy metal chromium (VI) contaminated soil: weigh 5 g of chromium-contaminated soil and place it in a 50 mL centrifuge tube. Add ultrapure water and then add 0.5 g of the magnetic biochar composite adsorbent prepared in this example. Flip and shake the mixture at 25° C. for 48 h. Separate the mixture with a magnetic bar that can absorb substances. Dry and digest the remaining soil. Use ICP-OES to determine the heavy metal chromium (VI) content in the filtrate. The heavy metal chromium (VI) ion removal rate is 89.2%.

[0082] Example 5

[0083] (1) The corn stalks were washed with deionized water to remove surface impurities, dried to constant weight, crushed with a grinder, and passed through an 80-mesh sieve;

[0084] (2) 140 mL of alkaline solution was mixed with 25 g of biochar and stirred at 160 rpm for 2.5 h at room temperature to remove impurities in the biochar;

[0085] (3) The biochar was rinsed with deionized water until the pH of the eluate was about 7.0. The wet biochar was dried in an oven at 60 °C for 12 h and then stored in a desiccator before use to obtain alkaline biochar;

[0086] (4) Alkaline biochar was added to 180 mL of 17% (w / v) PEI / methanol solution and stirred at 160 rpm for 24 h;

[0087] (5) Immediately transfer the stirred biochar to 100 mL of 5% (w / v) glutaraldehyde solution for crosslinking. Stir the solution at 160 rpm for 40 min. Then, wash with deionized water to obtain amino-modified biochar.

[0088] (6) 0.9 g of ferric chloride, 2.0 g of sodium acetate, 130 mg of sodium polyacrylate and 29 mL of ethylene glycol were placed in a reaction kettle and reacted at 195° C. for 9.5 h. After the reaction was completed, the reaction product was washed and vacuum dried to obtain carboxylated iron oxide magnetic nanospheres with rich carboxyl groups on the surface;

[0089] (7) 140 mg of carboxyferroferric oxide magnetic nanospheres were ultrasonically dispersed in 60 mL of MES (2-morpholineethanesulfonic acid) buffer solution, and 450 mg of EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride) and 750 mg of NHS (N-hydroxysuccinimide) were added to the above solution system and ultrasonication was continued for 60 seconds. The solution was then placed in a shaker at 37°C for 20 minutes and centrifuged quickly to obtain activated carboxyferroferric oxide nanoparticles. At the same time, 120 mg of amino-modified biochar was ultrasonically dispersed in 60 mL of PBS buffer, and the activated carboxyferroferric oxide nanoparticles were added, ultrasonicated quickly, and shaken in a shaker at 37°C overnight. The solution was magnetically separated and washed with water and ethanol three times, and then dried in an oven at 70°C for 12 hours to obtain a magnetic biochar composite adsorbent.

[0090] In order to verify the adsorption performance of the magnetic biocarbon composite adsorbent prepared in this example for heavy metals, the following tests were performed:

[0091] (1) A 300 mg / L heavy metal chromium (VI) solution was prepared, and the magnetic biochar composite adsorbent prepared in this example was added to the above solution at a dosage of 0.8 g / L. The solution was placed in a shaker and shaken at 160 r / min. 3 mL of samples were taken at intervals, and the samples were filtered through a filter membrane. The content of heavy metal chromium (VI) in the heavy metal chromium (VI) solution after adsorption by the adsorbent was determined using an ultraviolet spectrophotometer;

[0092]

[0093] Where R (%) is the removal rate of heavy metal chromium (VI) ions, C0 is the total heavy metal chromium (VI) concentration in the initial solution (mg / L), C e It is the concentration of heavy metal chromium (VI) ions in the solution at a certain time (mg / L).

[0094] (2) Prepare heavy metal chromium (VI) contaminated soil: weigh 5 g of chromium-contaminated soil and place it in a 50 mL centrifuge tube. Add ultrapure water and then add 0.8 g of the magnetic biochar composite adsorbent prepared in this example. Flip and shake at 25° C. for 48 h. Separate with a magnetic bar that can absorb substances. Dry and digest the remaining soil. Use ICP-OES to determine the heavy metal chromium (VI) content in the filtrate. The heavy metal chromium (VI) ion removal rate is 84.4%.

[0095] Example 6

[0096] (1) The corn stalks were washed with deionized water to remove surface impurities, dried to constant weight, crushed with a grinder, and passed through an 80-mesh sieve;

[0097] (2) 230 mL of alkaline solution was mixed with 45 g of biochar and stirred at 160 rpm for 1.5 h at room temperature to remove impurities in the biochar;

[0098] (3) The biochar was rinsed with deionized water until the pH of the eluate was about 7.0. The wet biochar was dried in an oven at 56 °C for 12 h and then stored in a desiccator before use to obtain alkaline biochar;

[0099] (4) Alkaline biochar was added to 120 mL of 12% (w / v) PEI / methanol solution and stirred at 160 rpm for 24 h;

[0100] (5) Immediately transfer the stirred biochar to 160 mL of 4% (w / v) glutaraldehyde solution for crosslinking. Stir the solution at 160 rpm for 45 min. Then, wash with deionized water to obtain amino-modified biochar;

[0101] (6) 1.0 g of ferric chloride, 3.5 g of sodium acetate, 50 mg of sodium polyacrylate and 31 mL of ethylene glycol were placed in a reaction kettle and reacted at 210° C. for 10.5 h. After the reaction was completed, the reaction product was washed and vacuum dried to obtain carboxylated iron oxide magnetic nanospheres with rich carboxyl groups on the surface;

[0102] (7) 150 mg of carboxyferroferric oxide magnetic nanospheres were ultrasonically dispersed in 70 mL of MES (2-morpholineethanesulfonic acid) buffer solution, and 490 mg of EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride) and 730 mg of NHS (N-hydroxysuccinimide) were added to the above solution system and ultrasonication was continued for 50 seconds. The solution was then placed in a shaker at 37°C for 25 minutes and centrifuged quickly to obtain activated carboxyferroferric oxide nanoparticles. At the same time, 110 mg of amino-modified biochar was ultrasonically dispersed in 70 mL of PBS buffer, and the activated carboxyferroferric oxide nanoparticles were added, ultrasonicated quickly, and shaken in a shaker at 37°C overnight. The solution was magnetically separated and washed twice with water and ethanol, and then dried in an oven at 65°C for 12 hours to obtain a magnetic biochar composite adsorbent.

[0103] In order to verify the adsorption performance of the magnetic biocarbon composite adsorbent prepared in this example for heavy metal chromium (VI), the following tests were performed:

[0104] (1) A 300 mg / L heavy metal chromium (VI) solution was prepared, and the magnetic biochar composite adsorbent prepared in this example was added to the above solution at a dosage of 0.8 g / L. The solution was placed in a shaker and shaken at 160 r / min. 3 mL of samples were taken at intervals, and the samples were filtered through a filter membrane. The content of heavy metal chromium (VI) in the heavy metal chromium (VI) solution after adsorption by the adsorbent was determined using an ultraviolet spectrophotometer;

[0105]

[0106] Where R (%) is the removal rate of heavy metal chromium (VI) ions, C0 is the total heavy metal chromium (VI) concentration in the initial solution (mg / L), C e It is the concentration of heavy metal chromium (VI) ions in the solution at a certain time (mg / L).

[0107] (2) Prepare heavy metal chromium (VI) contaminated soil: weigh 5 g of chromium-contaminated soil and place it in a 50 mL centrifuge tube. Add ultrapure water and then add 0.9 g of the magnetic biochar composite adsorbent prepared in this example. Flip and shake at 25° C. for 48 h. Separate with a magnetic bar that can absorb substances. Dry and digest the remaining soil. Use ICP-OES to determine the heavy metal chromium (VI) content in the filtrate. The heavy metal chromium (VI) ion removal rate is 86.8%.

[0108] In summary, the present invention prepares a novel amino-functionalized biochar by a surface chemical modification method, and combines it with carboxyl magnetic nanoparticles through a stable chemical covalent bond to prepare a novel magnetic biochar composite adsorbent. Through functional modification and surface modification, the prepared novel magnetic biochar composite adsorbent has both the excellent heavy metal chromium (VI) adsorption and removal ability of biochar and the excellent magnetic separation of magnetic nanoparticles, and can realize the efficient recycling and reuse of the adsorbent in the soil, which is in line with the development concept of green chemistry.

[0109] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a magnetic biocarbon composite adsorbent, characterized in that: The following steps are involved: 1) Washing, drying, crushing and sieving the waste biomass materials to obtain biochar raw materials, mixing the biochar raw materials with an alkaline solution to remove impurities, and then washing and drying to obtain alkaline biochar; The ratio of biochar raw material to alkaline solution is (20-50) g: (100-300) mL; the biochar raw material and alkaline solution are stirred at room temperature at a stirring speed of 120-180 rpm for 1-3 h to remove impurities in the biochar raw material; the biochar raw material is washed with water until the eluent is neutral, and the drying is carried out at 30-80 ° C for 12 h; 2) The alkaline biochar is fully mixed with a methanol solution of polyethyleneimine, and then cross-linked with a glutaraldehyde solution to obtain amino-modified biochar; 3) Ultrasonic dispersion of carboxyferroferric oxide magnetic nanospheres in 2-morpholineethanesulfonic acid buffer, and addition of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, and continued ultrasonic dispersion, followed by shaking on a shaker for 10-30 min, and centrifugation to obtain activated carboxyferroferric oxide nanoparticles; The dosage ratio of carboxyferroferric oxide magnetic nanospheres, 2-morpholineethanesulfonic acid buffer, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is (120-150) mg: (50-80) mL: (400-500) mg: (700-750) mg; The carboxyferroferric oxide magnetic nanospheres are synthesized by a one-step hydrothermal method, and the specific method is as follows: ferric chloride, sodium acetate, sodium polyacrylate and diethylene glycol are subjected to a hydrothermal reaction at 180-210° C. for 9-12 h according to a dosage ratio of (0.7-1.2) g: (2.0-4.0) g: (50-150) mg: (25-35) mL, and then washed and dried to obtain carboxyferroferric oxide magnetic nanospheres; 4) dispersing the amino-modified biochar obtained in step 2) in a buffer solution, adding the activated carboxyl ferroferric oxide nanoparticles obtained in step 3), mixing by ultrasonication, shaking on a shaker overnight, and washing and drying the product after magnetic separation to obtain a magnetic biochar composite adsorbent; The buffer solution used was PBS buffer, and the usage ratio of amino-modified biochar to PBS buffer was (80~120) mg: (50~80) mL.

2. The method for preparing the magnetic biocarbon composite adsorbent according to claim 1, characterized in that: In step 2), the amount ratio of alkaline biochar to the methanol solution of polyethyleneimine is (20~50) g: (50~200) mL; the mass concentration of the methanol solution of polyethyleneimine is 5%~20%, and the mixing is carried out at a stirring speed of 120~180 rpm for 24 h.

3. The method for preparing the magnetic biocarbon composite adsorbent according to claim 1, characterized in that: In step 2), the dosage ratio of alkaline biochar to glutaraldehyde solution is (20-50) g: (100-200) mL; the mass concentration of the glutaraldehyde solution is 1%-5%, and the cross-linking reaction is stirred at a speed of 120-180 rpm for 30-60 min.

4. The method for preparing the magnetic biocarbon composite adsorbent according to claim 1, characterized in that: The waste biomass material is corn straw, wheat straw or rice husk; the alkaline solution is 1-6 mol / L KOH solution.

5. A magnetic biocarbon composite adsorbent prepared by the preparation method described in any one of claims 1 to 4.

6. The use of the magnetic biocarbon composite adsorbent according to claim 5 in the adsorption of heavy metal chromium (VI), characterized in that: The magnetic bio-carbon composite adsorbent was treated in heavy metal chromium (VI) contaminated water for 48 hours, and the removal rate of heavy metal chromium (VI) ions reached 90.4%; the magnetic bio-carbon composite adsorbent was treated in heavy metal chromium (VI) contaminated soil for 48 hours, and the removal rate of heavy metal chromium (VI) ions reached 88.5%.

Citation Information

Patent Citations

  • Preparation method of graphene oxide and magnetic mesoporous silica composite material capable of adsorbing pollutants in water

    CN103432996A

  • Magnetic microsphere capable of absorbing cadmium ions and complexes thereof, as well as preparation method, application method and regeneration method of magnetic microsphere

    CN105536741A

  • Non-destructive repairing method for heavy metal contaminated soil

    CN105945044A

  • Preparation method of polyethyleneimine modified chitosan magnetic composite material

    CN112090406A